TRAINING FOR THE PUBLIC ACCOUNTING PROFESSION. - Claire, Richard S. (The Accounting Review, 1944)
Abstract Training for the public accounting profession is a continuing process. An accounting curriculum that is not up to date and does not provide men who are qualified to meet the current problems of public accounting practice is one to be avoided at all costs. Many public accounting firms today show more real concern over their social responsibilities and opportunities for real service to business than could be found in a group of typical accounting professors. The leading public accounting firms are today looking for men who have been broadly trained, who have a full understanding of the social responsibilities and standards of conduct which are required of those who enter the public accounting profession, and who are qualified to render to clients real services far beyond the scope of the ordinary audit. The author thinks that the public accounting profession may now be at that stage of growth and maturity where it would be glad to have the teaching profession provide training for various levels of public accounting responsibility and a limited amount of training along more specialized lines.